Influence of monsoon seasons on seagrass ecosystems on the coast of Kota Kinabalu (Sabah, Malaysia) - Mohd Azamuddin Mohd Hassan; Ejria Saleh; Rohana Tahir; John Madin (UNIMAS, 2025)
Seagrass beds in Kampung Kebagu, Kota Kinabalu, Sabah, are notably affected by natural events and human activities. Seasonal monsoons particularly the Northeast Monsoon (NEM) and the Southwest Monsoon (SWM), intensify these effects, causing significant changes to the seagrass beds in a short period. This study aimed to determine seagrass coverage and leaf length during the NEM and SWM at Kampung Kebagu. The leaf length was focusing on the dominant species; Inhauls a oroides along the transect line. This study was conducted within a year from February 2023 until January 2024 to cover both monsoon periods. Seagrass coverage was estimated using 50 cm × 50 cm (0.25 m2) quadrat with every 5 m interval along the transect line. Field measurements and data collection were done in February 2023, March 2023, May 2023, July 2023, September 2023, November 2023, and January 2024. The NEM was divided into two phases: February to March 2023 (T1) and November 2023 to January 2024 (T3). The SWM, identified as T2, spanned from May to September 2023. Further analysis of seagrass coverage and leaf length using Two-Way ANOVA was done to find significant effects of month between the parameters. There were significant different between seagrass coverage and months (p < 0.05). Seagrass coverage declined significantly to 38 ± 23% during the NEM but rebounded to 80 ± 11% in July 2023 during the SWM. The average leaf length of E. an oroides reached 29 ± 8 cm in May 2023 but was reduced to just 7 ± 2 cm by January 2024. Although this study was limited to a single year, it effectively captured fluctuations in seagrass coverage and leaf length across different seasonal monsoons. These results provide baseline data on how monsoon-related environmental changes affect seagrass ecosystems in this region.